NON-DEVELOPING PREGNANCY. THE ROLE OF HORMONAL CONTRACEPTION IN REHABILITATION TREATMENT - G. B. Dikke (Акушерство, гинекология и репродукция, 2016)
Non-developing pregnancy (NB) is main factor of reproductive losses. The stress developed after the NB like after the abortion which accompanied with excitation of the hypothalamic-pituitary system. This involves a violation of kind and rhythm of menstruation, with formation of anovulatory cycles. Its rationale to use modern low-dose COCs containing last generation progestagen desogestrel for restore menstrual and hormonal status. Contraception should be used to start first days during post-abortion period. The use of COCs could to prevent the occurrence of repeated unwanted pregnancies during post-abortion stress, to prevent development of complications and to normalize regulation of menstrual function and thereby ensure the enough time to restore women's reproductive health.